Immune Dysfunction is Associated with Readmission in Survivors of Sepsis Following Infected Pancreatic Necrosis - Yin J; Mao W; Xiao X; Yu X; Li B; Chen F; Lin J; Zhou J; Zhou J; Tong Z; Ke L; Li W (Dove Medical Press, 2021)
Jiangtao Yin,1,2,* Wenjian Mao,1,* Xiaojia Xiao,3 Xianqiang Yu,4 Baiqiang Li,5 Faxi Chen,5 Jiajia Lin,5 Jing Zhou,1 Jing Zhou,4 Zhihui Tong,5 Lu Ke,5 Weiqin Li1,5 1Department of Critical Care Medicine, Jinling Hospital, Nanjing Medical University, Nanjing, People's Republic of China; 2Department of Intensive Care Unit, Affiliated Hospital of Jiangsu University, Zhenjiang, People's Republic of China; 3Department of Critical Care Medicine, Jinling Hospital of Southern Medical University, Nanjing, People's Republic of China; 4Southeast University School of Medicine, Nanjing, People's Republic of China; 5Department of Critical Care Medicine, Jinling Hospital, Nanjing University, Nanjing, People's Republic of China*These authors contributed equally to this workCorrespondence: Lu Ke; Weiqin LiDepartment of Critical Care Medicine, Jinling Hospital, Medical School of Nanjing University, 305 East Zhongshan Road, Nanjing, 225001, People's Republic of ChinaEmail ctgkelu@nju.edu.cn; njzy_pancrea@163.comObjective: Immunosuppression is common in patients with infected pancreatic necrosis (IPN) and associated with morbidity and mortality. This study aimed to investigate the impact of immune status on mortality and readmission after hospital discharge in patients with IPN-related sepsis.Methods: In this prospective observational study, eligible adult patients with IPN-related sepsis requiring ICU admission were included. Monocytic human leukocyte antigen DR (mHLA-DR), expression of regulatory T cells (Treg), and neutrophil CD88 (nCD88) were measured on the diagnosis of sepsis, ICU discharge, hospital discharge, and 15, 30, 60 days after hospital discharge. Logistic regression model was used to assess potential risk factors for readmission 60-days within the index discharge.Results: A total of 53 patients were included, 13 died during hospitalization and one withdrew the consent soon after discharge. Among the survivors, a tendency of immune recovery was observed during the consecutive follow-ups, evidenced by the increased expression of mHLA-DR. Sixteen patients (41.03%) were readmitted within 60 days after the index discharge. In the multivariable regression model, APACHE II score when sepsis was diagnosed > 9 and mHLA-DR at discharged < 14,591 AB/C were found to be independent risk factors affecting readmission.Conclusion: Immunosuppression is common in patients with IPN-related sepsis and can persist until two months after discharge. The compromised mHLA-DR level at discharge was associated with readmission within two months after discharge.Keywords: infected pancreatic necrosis, sepsis, immunosuppression, monocyte HLA-DR, readmissions